2019
DOI: 10.1101/gad.329417.119
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of angiopoietin-like protein 2 signaling in tumor progression and anti-tumor immunity

Abstract: Angiopoietin-like protein 2 (ANGPTL2) is a secreted glycoprotein homologous to angiopoietins. Previous studies suggest that tumor cell-derived ANGPTL2 has tumor-promoting function. Here, we conducted mechanistic analysis comparing ANGPTL2 function in cancer progression in a murine syngeneic model of melanoma and a mouse model of translocation renal cell carcinoma (tRCC). ANGPTL2 deficiency in tumor cells slowed tRCC progression, supporting a tumor-promoting role. However, systemic ablation of ANGPTL2 accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…Our studies have revealed that nuclear-localized CTR1 plays a role in the growth recovery kinetics of Arabidopsis hypocotyls by increasing EIN3 stability. Given its negative roles in the ethylene response, the CTR1-mediated stimulation of the ethylene response in the nucleus was surprising; however, many proteins have dual functions in signal transduction pathways, and some perform opposite activities in the same biological process [54][55][56][57] . For example, in human memory control, AGAP3, an NMDA receptor-interacting signaling protein, not only enhances the activity of memory formation but also decreases the activity of memory formation, depending on the perception of different signals 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have revealed that nuclear-localized CTR1 plays a role in the growth recovery kinetics of Arabidopsis hypocotyls by increasing EIN3 stability. Given its negative roles in the ethylene response, the CTR1-mediated stimulation of the ethylene response in the nucleus was surprising; however, many proteins have dual functions in signal transduction pathways, and some perform opposite activities in the same biological process [54][55][56][57] . For example, in human memory control, AGAP3, an NMDA receptor-interacting signaling protein, not only enhances the activity of memory formation but also decreases the activity of memory formation, depending on the perception of different signals 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have revealed that nuclear-localized CTR1 plays a role in the growth recovery kinetics of Arabidopsis hypocotyls by increasing EIN3 stability via its interaction with EBFs. Given its negative roles in the ethylene response, the CTR1-mediated stimulation of the ethylene response in the nucleus was unforeseen; however, many proteins have dual functions in signal transduction pathways, and some perform opposite activities in the same biological process [37][38][39][40] . For example, in human memory control, AGAP3, an NMDA receptor-interacting signaling protein, not only enhances the activity of memory formation but also decreases the activity of memory formation, depending on the perception of different signals 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The retrovirus packaging cell line Platinum‐E (Plat‐E) (RRID:CVCL_B488) (Cell Biolabs Inc., San Diego, CA, USA) was maintained in DMEM supplemented with 10% FCS, 1 μg·mL −1 puromycin, and 10 μg·mL −1 blasticidin. The human renal tubular epithelial cell line HK‐2 (RRID:CVCL_0302) (ATCC, Manassas, VA, USA) harboring HA ‐ PRCC‐TFE3 (HK‐2/HA‐PRCC‐TFE3) [13] was maintained in DMEM/F‐12 supplemented with 10% FCS, 0.8 μg·mL −1 puromycin, and 10 μg·mL −1 blasticidin. All cell lines have been authenticated in the past 3 years by short tandem repeat analysis using the PowerPlex 16 HS System (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%